New York state folklife reader : diverse voices - Tucker, Elizabeth, 1948- (University Press of Mississippi, 2013)
New York and its folklore scholars hold an important place in the history of the discipline. In New York dialogue between folklore researchers in the academy and those working in the public arena has been highly productive. In this volume, the works of New York's academic and public folklorists are presented together. Unlike some folklore anthologies, New York State Folklife Reader does not follow an organizational plan based on regions or genres. Because the New York Folklore Society has always tried to ""give folklore back to the people, "" the editors decided to divide the edited.